Electron Catalytic Photochemical Cascade Carbodifluoroalkylation/Radical Cyclization of Methylene‐2‐oxazolines. Issue 10 (18th April 2017) - Qu, Chuanhua; Wu, Zhongkai; Li, Weipeng; Du, Hongbin; Zhu, Chengjian
Abstract: An operationally green, electron‐catalyzed, photochemical tandem carbodifluoroalkylation/radical cyclization of enol ethers is disclosed. The reactions occur via addition of difluoroacyl radicals to methylene‐2‐oxazolines and subsequent intramolecular base‐promoted homolytic alkyl substitution (BHAS) of the intermediate oxyl‐alkyl radicals. Initiation of the radical chain reaction is best achieved with a commercially available and cheap organic base, and readily accessible visible light is used as the energy source. Abstract :